Rare earth element patterns in a rapidly changing karst environment. (November 2022) - Katsanou, K.; Siavalas, G.; Panagopoulos, G.; Lambrakis, N.
Abstract: Samples of surface water, groundwater and rocks were collected along the Louros River karst system in Greece to study the evolution of the chemical composition of groundwater. It was found that the hydrochemistry is closely related to the lithology of the host rocks. Emphasis was placed on the study of REEs due to the presence of phosphate-rich rocks in the area. A distinctive feature that was also taken into account was the high velocities of surface and groundwater in this rapidly changing karst environment. The carbonate formations of the Ionian Zone determine the hydrogeology of the catchment, particularly the Senonian, Vigla and Pantokrator limestones, through which groundwater mainly moves at relatively high velocities, play a key role. From the northernmost areas at the upper part of the catchment to the southernmost areas at the river's mouth, a multitude of springs, along the river, mark the main base level, above which a common aquifer is formed on either riverbed, hydraulically and locally connecting those geological formations. The chemical composition of the water is mainly controlled by the dissolution of calcite, dolomite and gypsum, with Ca–HCO3 being the dominant water type. Elevated pH values (>7), increased concentrations of dissolved oxygen and low concentrations of Fe and Mn indicate a karst system with oxidising alkaline waters. Groundwater type changes when it encounters gypsum in the area, or when the process of dedolomitisation takes place and, together with the phosphate minerals contributes to the release of REEs into the water. ΣREEs range from 0.22 in anhydrite to 33.8 ppm in the sandstones. The REE concentrations in the 0.45 μm-filtered surface and groundwater samples range between 50 and 260 ng/L. REEs concentration in groundwater is controlled by pH. The European shale normalised REE profiles of the rock samples are enriched in LREEs compared to HREEs and show a slightly negative Ce anomaly, which is explained by an oxidising sedimentation environment. The positive Eu anomaly of the same samples was attributed to the presence of phosphate minerals. Positive anomalies in both Ce and Eu were observed in the corresponding profiles of surface and groundwater samples. The effect of carbonate species, especially HCO3 −, on surface and groundwater resulted in their enrichment in HREEs. In general, an enrichment of HREEs in surface and groundwater was observed in proportion to the distance covered. Highlights: Rainfall becomes immediately enriched in REEs. Rainwater and outcropping formations interaction leads to higher REEs in groundwater. The depositional environment is the key factor controlling REEs distribution in rocks. This is not the case for groundwater. Due to surface- and groundwater high flow and velocities REEs show low variability.